Testing for Linear and Log-Linear Regressions with Heteroscedasticity - TSE, Yiu Kuen (Institutional Knowledge at Singapore Management University, 1984)
This paper considers the problem of jointly testing for linear and log-linear regressions with heteroscedasticity. Lagrange multiplier tests are suggested; which do not require the heteroscedastic structures to be specified and are computationally easier than likelihood ratio tests.